Options for risk reduction in higher education - Vilmányi, Márton; Hetesi, Erzsébet; Veres, Zoltán (Marketing & Menedzsment, 2019)
The study seeks to indentify the various risks participants of higher education face and how these risks can be reduced. The aim of the research is to shed light on the factors influencing students in their assessment of the success of a given training. The factors are analysed in a given educational process and how they change in the spectrum of life-long learning timeframe. As a result of the research the existing gaps between institutional and student approach, expectations and competencies, along with the fundamental communication to reduce these gaps are explored. Furthermore, the results aim to explain the options available to reduce risk felt by students on the social and individual level and the kinds of communication that lead to student satisfaction and their consensus with the institution.